Management procedure development in RFMOs offer lessons for strategic and impactful stakeholder engagement and collaboration - Wilson, Ashley R.; Miller, Shana K.; Galland, Grantly R. (Frontiers in Marine Science, 2023)
International and domestic fisheries management bodies are increasingly embracing a management procedure (MP) approach to managing their living marine resources. An added advantage of an MP approach is the opportunity for strategic and impactful engagement and collaboration among resource managers, user groups, civil society and other stakeholder groups in MP development, adoption, and implementation. We consider examples from four regional fisheries bodies (i.e., RFMOs and a multi-lateral body) where stakeholders are contributing to the development of MPs for several stocks to varying degrees. These case studies highlight differing structures and processes for open and transparent stakeholder engagement in management strategy evaluation (MSE) and MP development. We identify that one important difference between sufficient and insufficient stakeholder engagement in these cases is the presence or absence of formalised structures and processes for inclusive and open stakeholder engagement, where there are key roles for stakeholder inputs and feedback during key stages of MSE and MP development. We highlight the benefits of engaging stakeholders from the outset of the MP development process, including designing processes, agreeing on the timelines and workplan for MSE and providing inputs that can lead to the successful adoption of an appropriate MP. We then consider how stakeholder engagement may be improved in other multi-lateral regional fisheries bodies, such as the NEAFC/ Northeast Atlantic coastal States management forums, as well as other relevant RFMOs.